Reduced Graphene Oxide Carbon Yarn Electrodes for Drug Sensing - Sriprasertsuk, Sutthima; Zhang, Shuai; Wallace, Gordon; Chen, Jun; Varcoe, John R.; Crean, Carol (Frontiers in Sensors, 2021)
A modified carbon fibre yarn sensor was developed for the voltammetric determination of paracetamol and its interferents (dopamine and ascorbic acid). Reduced graphene oxide (rGO) was electrochemically deposited onto a carbon fibre yarn. Further modification was achieved using polypyrrole (PPy) coated onto the rGO carbon fibre yarn via electropolymerisation of pyrrole with cyclic voltammetry (CV). The surface of the rGO and PPy-rGO carbon fibre electrodes were characterised using Raman spectroscopy and scanning electron microscopy. The rGO and PPy-rGO carbon fibres had a 3.5-fold and 7-fold larger electrochemical surface area compared to bare carbon fibre (calculated using the Randles-Sevcik equation). Two clearly distinguished oxidation peaks at 0.49 V and 0.25 V (vs. Ag/AgCl) were observed at the rGO fibre electrode during the simultaneous detection of paracetamol and dopamine, respectively, by CV. The detection limit (3σ S/N) of the rGO carbon fibre electrode for differential pulse voltammetry (DPV) determination of paracetamol was at 21.1 µM and 6.0 µM for dopamine. In comparison, the simultaneous determination of paracetamol and dopamine by CV at the PPy-rGO fibre electrode gave oxidation peaks of paracetamol and dopamine at 0.55 V and 0.25 V (vs. Ag/AgCl), respectively. The detection limit (3σ S/N) for paracetamol was notably improved to 3.7 µM and maintained at 6.0 µM for dopamine at the PPy-rGO carbon fibre electrode during DPV.